An Analysis of Health Situation of Women and Children at the Char of Gangachara Upazilla: A GIS based Case Study (Global Journal of Human-Social Science, 2016)
Every year in Bangladesh substantial life of women and children are lost through various diseases. The study area of Gangachara is one of the monga-prone areas in Bangladesh. The river, Tista has a big influence on the livelihoods of the people of Gangachara. Healthcare situation in the chars is poor. But health is a basic requirement to improve the quality of life. Floods and erosion disrupted the lives of char dwellers. The victims of erosion lose their settlements, agricultural lands and employment and are forced to move elsewhere sometimes on a yearly basis. Bangladesh is still lagging behind in the field of environmental health. The Level of morbidity remains very high in Bangladesh. Much of the sickness, ill health and resultant deaths in this country are due the overall degradation of the environment. More than 80% population in Bangladesh live in rural areas and environmental problems are more acute in the rural areas of the country.
Keywords: women; children; health situation; gangachara; GIS